1999
DOI: 10.1016/s0378-1097(99)00530-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of light on germinating spores of Streptomyces viridosporus

Abstract: Our study showed that the effect of light on germinating spores of Streptomyces was variable : some species were indifferent, whereas others, such as Streptomyces viridosporus, displayed a marked inhibition of CFU numbers on growth medium. A special study with S. viridosporus showed that light only had an impact during the first few hours of spore incubation. The effects of scavengers of toxic forms of oxygen and of photosensitizers, along with the oxidative stress of illuminated spores evidenced by the supero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…S. coelicolor spores contain endogenous sources of nutrients such as trehalose (19,20), and it may be that growth arrest is a manifestation of a switch by the extending tip from an endogenous to an exogenous energy source or even a redeployment of nutrient resources within the microcolony. We were unable to generate movies of FtsZ-EGFP during germination, which is perhaps due to the inhibitory effects of light during spore germination seen in some streptomycete species (15). Following germination, hyphal extension occurred at a rate of ϳ20 m h Ϫ1 and FtsZ-EGFP rings were laid down ϳ56 m behind the growing tip.…”
Section: Discussionmentioning
confidence: 99%
“…S. coelicolor spores contain endogenous sources of nutrients such as trehalose (19,20), and it may be that growth arrest is a manifestation of a switch by the extending tip from an endogenous to an exogenous energy source or even a redeployment of nutrient resources within the microcolony. We were unable to generate movies of FtsZ-EGFP during germination, which is perhaps due to the inhibitory effects of light during spore germination seen in some streptomycete species (15). Following germination, hyphal extension occurred at a rate of ϳ20 m h Ϫ1 and FtsZ-EGFP rings were laid down ϳ56 m behind the growing tip.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, S. mycarofaciens SS‐2‐243 had a significantly higher growth rate in the dark condition than in the light condition. This was due to the fact that light remarkably inhibited the spore germination as also found in S. viridosporus and S. coelicolor [40]. The influence of light on the growth of various Streptomyces spp.…”
Section: Discussionmentioning
confidence: 98%
“…S. phaeopurpureus 5125, S. salmonicida 5472, and S. fulvissimus could grow well in light conditions [27]. On the other hand, S. viridosporus, S. lividans , and S. coelicolor were sensitive to light, while S. ambofaciens and S. pilosus remained unchanged and unaffected [40]. It has been demonstrated that light conditions influenced the growth of Streptomyces spp.…”
Section: Discussionmentioning
confidence: 99%
“…Different previous studies have shown that S. phaeopurpureus 5125, S. salmonicida 5472, and S. fulvissimus could grow well in light conditions (Koyama et al 1975). Some strains of Streptomyces species such as S. viridosporus, S. lividans and S. coelicolor were reported to be sensitive to light, while others remained unaffected (S. ambofaciens and S. pilosus) (Imbert and Blondeau 1999). It has been demonstrated that light conditions in uenced the growth of Streptomyces sp.…”
Section: Discussionmentioning
confidence: 99%